Propagandawagen voor de demonstratie van 13 april 1935 in Den Haag. Uit: Coll. Diepenhorst, album 27
Propagandawagen voor de demonstratie van 13 april 1935 in Den Haag. Uit: Coll. Diepenhorst, album 27.